Pillars of artificial intelligence - Neukart, Florian (Reverse Engineering the Mind, 2016)
The major goal of this elaboration is to work out how specific aspects of the human mind, namely those responsible for higher cognitive functions, function, and to figure out which hardware is required to process an artificial mind with the same, similar or superior capabilities. For this, I will focus on any approach that allows us to reproduce cognitive capabilities, but not necessarily achieve this target by the same means as evolution did. It makes sense, at this point, to provide an introduction to artificial intelligence in order to understand which areas of the neocortex are subject to AI research and development.